2008
DOI: 10.1111/j.1572-0241.2008.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interferon-Gamma Release AssayVersusTuberculin Skin Test for Tuberculosis Screening in Inflammatory Bowel Disease

Abstract: Agreement between the two test methods is poor in IBD patients. In contrast to the QFT-G-IT test, the TST is negatively influenced by immunosuppressive medication and vaccination status, and should thus be replaced by the IGRA for TB screening in immunosuppressed patients having IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 39 publications
6
74
3
5
Order By: Relevance
“…The sensitivity and specificity of IGRA in older children exposed to index cases are similar compared to adults, as long as they are not infected by HIV; although a few studies have shown a lower sensitivity for IGRA tests in very young children (25,53,54). The lower sensitivity found for both TST and IGRAs among very young children might be explained by immune immaturity or having a population with underlying conditions that may interfere with immunity, such as co-infections with helminthes and malnutrition; although BCG is not expected to interfere with IGRAs (55).…”
Section: B) Childrenmentioning
confidence: 98%
“…The sensitivity and specificity of IGRA in older children exposed to index cases are similar compared to adults, as long as they are not infected by HIV; although a few studies have shown a lower sensitivity for IGRA tests in very young children (25,53,54). The lower sensitivity found for both TST and IGRAs among very young children might be explained by immune immaturity or having a population with underlying conditions that may interfere with immunity, such as co-infections with helminthes and malnutrition; although BCG is not expected to interfere with IGRAs (55).…”
Section: B) Childrenmentioning
confidence: 98%
“…A study conducted in Brazil, where tuberculosis is endemic, showed that the PPD was not very effective in detecting LTB in patients with rheumatic diseases before undergoing biological therapy [6]. In recent years, new methods for detecting tuberculosis based on quantification of gamma-interferon after stimulation with specific antigens, known as IGRA (Interferon-Gamma Release Assay), have shown better results than PPD, including in immunosuppressed patients [7]. However, in a recent publication, Wong SH et al demonstrated that IBD patients on immunosuppressive therapy had a significantly lower IGRA positive rate (13.0% versus 29.6%; P = 0.002) compared to immunosuppressant-naive IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in subjects vaccinated with BCG, the specificity of QFT-G was 96% (95%CI: 94%-98%) while that of TST was only 59% (95%CI: 46%-73%). A Swiss study has compared TST and QFT-G performances in IBD patients [17] . The studied population comprised 114 patients with Crohn's disease (CD), 44 with ulcerative colitis (UC), 10 with indeterminate colitis and 44 control subjects.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%